2014
DOI: 10.1136/bcr-2014-205808
|View full text |Cite
|
Sign up to set email alerts
|

Paratesticular sarcomas: two cases with different evolutions

Abstract: SUMMARY Paratesticular sarcomas are rare and account for less than 1% of all adult sarcomas. Intrascrotal tumours can be testicular or paratesticular, paratesticular tumours being rarer (7-10%). Only 30% of paratesticular tumours are malignant and 90% of these are sarcomas. Histological subtypes include leiomyosarcoma, rhabdomyosarcoma, liposarcoma and undifferentiated high-grade pleomorphic sarcoma. Recurrence is frequent in this type of tumour and can occur years from initial diagnosis. These reports show tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 9 publications
0
10
0
5
Order By: Relevance
“…8,9 Rhabdomyosarcomas have a propensity to affect males in the first two decades of life and tend to be a more aggressive subtype. 7 Differentiation between the benign and malignant lesions by clinical examination alone is rarely accurate, let alone differentiation of tumour type, 9 thus further characterisation with imaging, namely ultrasonography is required. 10 This is of importance due to the radical nature of the resection in malignant cases (often requiring hemiscrotectomy and high cord ligation) when compared with simple excisions for benign tumours.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 Rhabdomyosarcomas have a propensity to affect males in the first two decades of life and tend to be a more aggressive subtype. 7 Differentiation between the benign and malignant lesions by clinical examination alone is rarely accurate, let alone differentiation of tumour type, 9 thus further characterisation with imaging, namely ultrasonography is required. 10 This is of importance due to the radical nature of the resection in malignant cases (often requiring hemiscrotectomy and high cord ligation) when compared with simple excisions for benign tumours.…”
Section: Introductionmentioning
confidence: 99%
“…2 The majority of all paratesticular masses are benign and include lipomas, adenomatoid tumours and leiomyomas, however fewer than a third are malignant with 90% of these being sarcomas. 3 Malignant sarcomas include liposarcomas, rhabdosarcomas, and leiomyosarcomas as the most common three variants, with malignant fibrous histiocytomas or dedifferentiated sarcomas also being seen [4][5][6] (see Table 1). The majority of paratesticular sarcomas arise from the spermatic cord.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, paratesticular RMS is rare in adults but often occurs in children, representing 7 to 10% of the tumors in male genitourinary system ( 12 ). Thus, since it’s uncommon in adults, few studies have reported paratesticular eRMS ( 13 , 14 ). Pathologically, the eRMS presents the existence of poorly differentiated cells and rhabdomyoblasts, with abundant eosinophilic cytoplasm indicating embryonal rhabdomyosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Paratesticular tumors are rare comprising 7-10% of total intrascrotal tumors of which 70% are benign and 30% are malignant. [1] Leiomyoma and undifferentiated pleomorphic sarcoma are two such rare tumors which should be accurately diagnosed for purpose of treatment and prognosis. Scrotal leiomyomas are essentially benign arising from the subcutaneous tissue or dartos muscle.…”
Section: Introductionmentioning
confidence: 99%